Perancangan Media Pembelajaran Interaktif Berbasis Android Menggunakan App Inventor 2 Pada Mata Pelajaran Biologi - Mursyidin, Mursyidin; Dewi, Sarini Vita; Khairi, Muhammad Sajadal (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2024)
Biology requires complex learning because of its abstract and detailed concepts. Using Android applications can increase student interest and involvement in learning. An Android-based application designed with App Inventor 2 can be a solution for developing interactive Biology learning media. This research aims to design Android-based Biology learning media using App Inventor 2 which can improve students' understanding. The research method used is Research and Development (R&D) which includes observation, planning, product design, product development and product validation. The validators involved in this research consisted of three media experts and three subject matter experts. The research respondents were 25 class X students who took Biology as a subject. Random sampling techniques are used to select the sample, ensuring that each member of the population has an equal chance of being selected. The Android-based Biology learning application developed in this research was rated "Very Appropriate" with an average score of 4.3 on a scale of 1-5. Student responses to the Android-based Biology learning application also show the "Very Good" category with an average score of 4.4 on a scale of 1-5. The Android-based Biology learning application developed has proven to be feasible and effective in learning Biology, especially in the subtopics of fungi, plants and animals.